2021
DOI: 10.3168/jds.2020-19604
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of Staphylococcus aureus and methicillin-resistant Staphylococcus aureus isolated from retail yak butter in Tibet, China

Abstract: This study aimed to investigate the prevalence, molecular characteristics and antibiotic resistance of Staphylococcus aureus isolates from yak butter in Tibet, China. A total of 218 yak butter samples were collected from retail stores in Tibet and screened for Staph. aureus. Furthermore, the virulence genes, resistance genes, antimicrobial susceptibility, and molecular typing [pulsed-field gel electrophoresis (PFGE), multilocus sequence typing, and staphylococcal protein A (spa) typing] of Staph. aureus isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Similarly, in the research conducted by Zhang et al . (2023b), the segment with an MW ranging from 2000 to 3000 Da, derived by Flavourzyme from yak casein, exhibited superior antibacterial activity against S. aureus . The peptide fraction with a MW below 3000 Da demonstrated the higher antibacterial activity among all fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the research conducted by Zhang et al . (2023b), the segment with an MW ranging from 2000 to 3000 Da, derived by Flavourzyme from yak casein, exhibited superior antibacterial activity against S. aureus . The peptide fraction with a MW below 3000 Da demonstrated the higher antibacterial activity among all fractions.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with our findings, the antibacterial peptide APKHKEMPFPKYP derived from yak casein maintained a positive charge at neutral pH. This peptide was composed of 53.85% hydrophobic amino acids, with the K prominently featured within its sequence (Zhang et al ., 2023b). This peptide was predicted to have a strong affinity toward DNA gyrase and DHFR, two critical enzymes for sustaining bacterial growth, through various noncovalent bonds such as salt bridges, π–π stacking, hydrogen bonds and hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…In the neighboring country, India, Ganai et al [ 48 ] reported that 44.1% of the S. aureus isolates were MRSA. Other studies conducted in Turkey, Egypt, China, and Algeria reported 75.4%, 35.7%, 9.61%, and 4.1% prevalences of MRSA [ 49 , 50 , 51 , 52 ]. The main causes of increased MRSA prevalence are the irregular use of beta-lactam antibiotics and poor hygienic conditions during milking [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several isolates collected from livestock were included in the evolutionary tree. These livestock-associated strains were almost all MSSA and distributed worldwide and were interspersed with human strains in the same clades, although some studies have reported that the livestock-associated ST1 strains emerged in China [ 10 , 39 , 40 ]. However, the lack of complete genome information is a limitation to further analyse the relationship between the livestock-associated ST1 in China and the clinical ST1 in our study.…”
Section: Discussionmentioning
confidence: 99%